Personalized Arts Learning Through Musical Preferences and Personality Traits: A Conceptual Study Using the 16PF Model - Bayu Aji Wicaksono; Warih Handayaningrum; Eko Wahyuni Rahayu; Umi Anugerah Izzati (Universitas Negeri Semarang, 2025)
This conceptual study examines how musical preferences reflect personality traits, using Raymond Cattell’s 16 Personality Factors (16PF) as a theoretical lens to inform personalized strategies in arts education. Through an integrative qualitative literature review, it synthesizes insights from music psychology, personality theory, and affective pedagogy to develop a framework for emotionally resonant and cognitively responsive learning environments. Findings indicate that preferences for genres such as classical, jazz, pop, or hip-hop are closely linked to psychological traits like sensitivity, liveliness, openness to change, rule-consciousness, and social boldness. These associations enable educators to identify students’ affective orientations and adapt arts instruction to their individual learning styles and emotional needs. The proposed framework addresses key educational challenges such as emotional disengagement and cognitive fatigue by positioning music as both a reflective medium and a pedagogical tool for fostering self-awareness and personal expression. It further advocates the use of informal assessments and personality profiling to support differentiated instruction and culturally relevant curriculum design. The study contributes a theoretically grounded pedagogical model that integrates personality-informed strategies with student-centered approaches, enhancing learner engagement, authenticity, and inclusion. Ultimately, this research offers a conceptual foundation for arts education that is more personalized, emotionally intelligent, and psychologically responsive.